Phát triển năng lực thiết kế bài học theo hướng tìm tòi - khám phá với sự hỗ trợ của trí tuệ nhân tạo tạo sinh cho sinh viên sư phạm tiểu học - Lê Thị Hồng Chi , Lê Thị Hồng Chi (Tạp chí Giáo dục, 2026)
The 2018 General Education Program emphasizes the development of students' competencies and qualities, with lesson design based on the inquirybased learning (IBL) approach being a crucial requirement for primary school teachers. However, preservice teachers face challenges in constructing and assessing inquiry-based activities. This study proposes a competency framework for lesson design using the IBL approach with the support of generative artificial intelligence (GenAI) for preservice primary school teachers, consisting of ten competency components and a five-step competency development process. The findings show that GenAI does not replace but acts as a collaborative partner, helping students become more creative and transparent in their lesson design. Thisresearch contributesto the theoretical framework on integrating IBL and AI in teacher education and has practical implications for improving the “Teaching Methodology” course.